Dry gas seals handbook - Stahley, John S. (PennWell Corp., 2005)
Annotation Despite the fact that the use of dry gas seals in process gas centrifugal compressors has increased dramatically over the last 20 years, the technology remains misunderstood by many in the industry. Dry gas seals operate with clearances measured in microns, much less than the thickness of a human hair! While dry gas seals can be very problematic if not properly applied at the time of plant, process, and/or compressor design, the many successful installations are a testament to how trouble-free these devices can be when properly applied. Let author John Stahley help you take the mystery out of dry gas seals in this comprehensive new book. Dry gas seals are in used in compressor stations, processing plants, refineries, chemical plants, and more. This book is perfectly suited for: _ Engineers _ Operators _ Maintenance personnel _ Purchasing personnel _ Technical management The information found in Dry Gas Seals Handbook will help you make informed decisions regarding the application, operation, and maintenance of dry gas seals. This book presents a complete guide to the technology, from the principle of gas seal operation to _lessons learned_ from actual field experience. Key features & benefits: _ More than 50 figures to illustrate explanations _ Seven case studies break down common problems associated with dry gas seals, corrective actions, and lessons learned _ Appendices provide typical examples of dry gas seal test reports and dry gas seal and barrier seal selection guidelines _ Glossary of common terms related to dry gas seal technology.
Title from title screen.
Keywords: Sealing (Technology) -- Handbooks, manuals, etc.; Natural gas -- Handbooks, manuals, etc.; elektronické knihy; electronic books